Enterococcus Faecalis and Its Influence of the Success of Endodontic Treatment - K. Alinčová; R. Slezák (Czech Dental Chamber, 2010)
The aim of this review article was an overview about Enterococcus faecalis and effective working process during the treatment of root canals in order to precede failure of the endodontic therapy as the consequence of the presence of this bacterium. Enterococcus faecalis is isolated significantly more often from secondarily treated root canals. It seems to colonize the dental root canal system likely by the transmission from oral cavity within the root canal treatment as the consequence of an insufficient asepsis control or through temporary or definitive filling leakages in the crown part of the tooth. The exogenic source of the infection is likely food. The risk of the infection by this bacterium rises in presence of the insufficient oral hygiene and manifestations of various infectious diseases associated with dental plaque cummulation.